The Prominence of IoT in Enhancing Business Success in the Context of Industry 4.0 - Kiradoo, Giriraj (Recent Progress in Science and Technology Vol. 6, 2023)
The IoT is emerging as an increasingly pivotal component of contemporary business and commerce, especially within the context of Industry 4.0, which embodies the trend of automation conjoined with data exchange in various industries, including manufacturing. The primary aim of this research paper was to investigate the significance of IoT in enhancing business success within the framework of Industry 4.0. Qualitative methodology was employed to gather data from literature reviews and case studies of companies successfully integrating IoT into their operations. The study revealed that cloud computing, edge computing, actuators, artificial intelligence, machine learning, and blockchain are crucial IoT technologies that enable businesses to automate processes, improve device communication, and securely store and manage data. Furthermore, the study found that IoT technologies such as connected devices, sensors, and big data analytics are essential for enhancing business operations, lowering costs, and enhancing productivity. By enabling real-time monitoring and control of processes, IoT facilitates informed decision-making and swift response to market changes, ultimately leading to improved customer experiences through personalised and customised services and valuable insights into customer behaviour. In light of the constantly evolving market, businesses that adopt IoT technologies are more likely to remain competitive and ensure long-term success. The study underscores businesses' need to invest in IoT technologies to maintain competitiveness and achieve sustained success.